La femme « psychiatrisée » en milieu carcéral - Germain, Daniel (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1988)
The author, a nurse in a detention centre for women, describes the clientele of the psychiatric section, the activities and services offered to them as well as his own work with inmate patients.